The Complexities of Antimicrobial Resistance in Acute Care: An Exploration of Key Actors and Factors Associated with Acute Care Antimicrobial Stewardship - Hughes, John Gerard (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2022)
Background Antimicrobial resistance (AMR) is an evolving global healthcare emergency, of which a significant driver is the use and overuse of antimicrobials. Antimicrobial stewardship (AMS) is a multi-component, multidisciplinary approach to addressing AMR by ensuring optimal antimicrobial use and minimising patient adverse outcomes. The hospital environment is an important context within which antimicrobials are used, owing to higher levels of patient co-morbidity and acuity. Ensuring that hospital based AMS programmes are fit for purpose and suited to the local clinical and cultural context will help ensure positive patient outcomes. Owing to the paucity of such research carried out in Irish acute care settings, this research aimed to investigate the actors, and associated factors, associated with antimicrobial use in the largest public acute hospital in Ireland. In doing so, a further aim was to postulate behaviour change strategies targeting these actors to optimise the impact of the St James s Hospital (SJH) AMS programme. Methods Hospital clinicians (medical doctors, surgeons, nurses and pharmacists) and hospital inpatients were recruited as key stakeholders in acute care AMS. The hospital patient council were invited as research collaborators. Recognising the hospital environment as a complex adaptive system, a mixed methods data collection approach was used, incorporating evidence synthesis, clinical audit, quantitative surveys, qualitative focus groups and interviews. Data was analysed through thematic analysis, the Capability Opportunity-Motivation behaviour model, the Theoretical Domains Framework and the Behaviour Change Wheel. Behaviour change strategies were suggested using the Behaviour Change Taxonomy. Results In total, data was collected from 154 healthcare professionals and 60 patients, while prescribing metrics for 1929 antimicrobial prescriptions were audited. Both quantitative and qualitative data described better antimicrobial prescribing performance among medical specialities in comparison to their surgical counterparts. Sociocultural and socio-professional nuances associated with antimicrobial use in hospital were identified among clinicians and patients. Junior doctors were found to be influenced by the antimicrobial prescribing habits of their senior colleagues, while these senior prescribers are influenced by risk avoidance in the form of overtreatment with antimicrobials. Patients reported reluctance to engage with antimicrobial prescribing quality in hospital and receive little opportunity to do so, but clinicians would welcome this type of engagement. These data, combined with the findings from a scoping review on the use of complexity theory in AMS, drove the design of two behavioural change strategies. These strategies are directed at clinicians and patients, to leverage their engagement towards prudent antimicrobial use in hospital. A strategy for providing antimicrobial prescribing feedback was also suggested to ensure its feasibility, relevance and adoption in practice. Patient representatives collaborated as research partners and reported positive feedback to their inclusion and perceived impact on patient engagement studies. Conclusion In line with emerging acute care AMS literature, this research explored the dynamics of key actors on antimicrobial use at SJH, from a social science perspective using mixed methods. There is a paucity of mixed methods, social science orientated AMS research conducted in Ireland; this is the first such research conducted in an Irish acute care hospital. Findings will now be used to inform the future strategy and operations of the SJH AMS programme. While the results may not be transferrable to other institutions, future work at individual hospitals should consider these strategies for local piloting, evaluation and adoption.
APPROVED
Keywords: antimicrobial stewardship; antimicrobial resistance; health services research; mixed methods